IMPLEMENTASI NILAI-NILAI BUDAYA MINANGKABAU DALAM AKTIVITAS USAHA (STUDI ETNOGRAFI PADA USAHA RUMAH MAKAN PADANG) - LV, YUHENDRI; DARMAWAN, ALDI (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aims to analyze the implementation of Minangkabau cultural values ​​in the business activities of Padang Restaurants and their role in maintaining business sustainability. The study uses a qualitative approach with an ethnographic type. Research informants consist of owners and managers of Padang Restaurants selected purposively. Data collection techniques include participatory observation, in-depth interviews, and documentation, while data analysis is carried out inductively through Spradley's ethnographic stages. The results show that Minangkabau cultural values ​​such as the adat basandi syarak, syarak basandi Kitabullah, the principle of deliberation and consensus, the matrilineal kinship system, and the work ethic ka awak ka urang are implemented in business management, customer service, and business decision-making. The implementation of these values ​​contributes to consumer trust, customer loyalty, and the business activities of Padang Restaurants.